PENINGKATAN KOMPETENSI GURU SD AL KAUTSAR TENTANG BULLYING DAN KEKERASAN DI SEKOLAH - Kusnadi, Starry Kireida; Zuroida, Aironi; Nurlaily, Lutfiana; Lestari, Bayu Andriyani Wahyuning (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Bullying is a form of aggressive action, violence, hurting others that is carried out continuously. The causes are diverse, ranging from a family environment that is always fighting, less educational shows, a less child-friendly community environment and even teachers who still do not fully understand how to overcome bullying behavior in schools. One of the factors causing bullying behavior is a school situation that is not harmonious or discriminatory. Sometimes the phenomenon of bullying that occurs in schools is not realized by the school and parents. Most parents and school authorities consider the habit of disturbing friends, arguing, and mocking each other as a common behavior among school children and not a threatening thing. The problems faced by SD Al Kautsar Surabaya are classified into 3 aspects, namely cognitive aspects, affective aspects and psychomotor aspects. The cognitive aspect is the lack of knowledge and understanding about bullying and violence. The affective aspect is the lack of understanding of the psychological impact of bullying and violence. While the psychomotor aspect is the lack of preventive and handling actions against bullying and violent behavior. The solution to the problem is to provide workshops to increase the competence of SD Al Kautsar Surabaya teachers in understanding bullying and violence, as well as providing assistance to form an anti-bullying and violence task force at school as an effort to reduce cases of bullying and violence. The output targets to be achieved are measuring with pretests and posttests to teachers to determine the extent of the increase in teacher competence regarding bullying and violence, teachers better understand the psychological conditions of the impact of bullying and violence, and teachers can have effective prevention and handling actions. From this assistance, it is hoped that teachers will be more aware, sensitive, alert and understand the psychological conditions of students and have effective preventive and handling actions against bullying and violent behavior that occurs in schools. The implementation method used in this program is through workshops and mentoring carried out in stages related to bullying and violence (providing material, film screenings, case studies, discussions, ice breaking, games facts or myths related to bullying and violence).